Ribonucleotide reductase activity is coupled to DNA synthesis via proliferating cell nuclear antigen. - Salguero, I; Guarino, E; Shepherd, M; Deegan, T; Havens, C; MacNeill, SA; Walter, J; Kearsey, S (2012)
Synthesis of deoxynucleoside triphosphates (dNTPs) is required for both DNA replication and DNA repair and is catalyzed by ribonucleotide reductases (RNR), which convert ribonucleotides to their deoxy forms [1, 2]. Maintaining the correct levels of dNTPs for DNA synthesis is important for minimizing the mutation rate [3-7], and this is achieved by tight regulation of RNR [2, 8, 9]. In fission yeast, RNR is regulated in part by a small protein inhibitor, Spd1, which is degraded in S phase and after DNA damage to allow upregulation of dNTP supply [10-12]. Spd1 degradation is mediated by the activity of the CRL4(Cdt2) ubiquitin ligase complex [5, 13, 14]. This has been reported to be dependent on modulation of Cdt2 levels, which are cell cycle regulated, peaking in S phase, and which also increase after DNA damage in a checkpoint-dependent manner [7, 13]. We show here that Cdt2 level fluctuations are not sufficient to regulate Spd1 proteolysis and that the key step in this event is the interaction of Spd1 with the polymerase processivity factor proliferating cell nuclear antigen (PCNA), complexed onto DNA. This mechanism thus provides a direct link between DNA synthesis and RNR regulation.